2021
DOI: 10.1155/2021/4107743
|View full text |Cite|
|
Sign up to set email alerts
|

The Application Value of MRI in the Training and Physical Rehabilitation of Gastrocnemius with Acute Sports Injury

Abstract: The purpose of this study was to analyze the magnetic resonance imaging (MRI) signs of acute gastrocnemius injury and to provide the basis for clinical diagnosis. Thirty-two patients with acute gastrocnemius muscle injury (19 males and 13 females, aged 18–63 years, mean 46 years) were recruited, and MRI scans were performed. The results showed that all the lesions of calf gastrocnemius were detected in 32 patients, including first-degree injury in 15 cases, second-degree injury in 15 cases, and third-degree in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%